PERMASALAHAN HUKUM PENGALIHAN RISIKO KREDIT SINDIKASI MELALUI INSTRUMEN CREDIT DERIVATIVE - Handriyanto Wijaya (Fakultas Hukum Universitas Kristen Indonesia, 2020)
The main function of a bank is as an institution that collects and distributes public funds. Credit isthe main activity of a bank's business to channel funds to the public. One legal basis for grantingcredit is by agreeing on a credit agreement. In granting loans in a very large amount, thenusually the bank will provide syndicated loans. Lending is dedicated credit lending by involvingmore than one bank, not only domestic banks but also by foreign banks. In providing syndicatedloans, it is common practice to transfer syndicated loans to other parties as stipulated in thesyndicated loan agreement. The transfer of syndicated loans to other parties is a right owned bythe creditor which is indispensable in order to avoid credit risks related to violations of the LegalLending Limit (BMPK) to debtors as well as to overcome the liquidation problems of banksparticipating in the syndicated loan agreement. Credit Derivative (CD) is a financial instrumentby transferring some or all of the risk of debtor debt obligations from one party to another party.The CD instrument was issued for the benefit of syndicated creditors in anticipation of default bydebtors. The CD instruments used in transferring syndicated credit risk include Credit DerviativeSwaps (CDS), Credit Linked Notes (CLN), Total Return Swaps (TRS) and Total Rate of ReturnSwaps (TRORS). Keywords: Credit Risk; Credit Derivative and Sydicated Loan.